Avaliação do serviço de proteção e atendimento integral à família (PAIF) em Maracanaú/CE: as (re)construções da política em contexto de pandemia - Braga, Jamille Rodrigues (2022)
The present work aimed to evaluate the Service of Protection and Integral Assistance to the Family (PAIF), executed in the Social Assistance Policy in Maracanaú/CE, in the context of a pandemic. The specific objectives intended to analyze how the family dimension is addressed in the legal frameworks of the Social Assistance Policy in correspondence with the daily life of the service, to understand how PAIF professionals perform the service at CRAS Pajuçara and to understand how PAIF achieves, in context of a pandemic, the women of the Social Assistance Policy in Maracanaú/CE. We seek to understand the obstacles and possibilities of operationalization of the service, bringing to the discussion the family and gender dimension, having as a horizon the guarantee of rights, in the context of dismantling of social policies, through the performance of the multiprofessional team in the Reference Center of Social Assistance (CRAS) Pajuçara. We question the conceptual bases, trajectories and the socioeconomic and political context of this public policy. In the methodological aspects, we chose to carry out an in-depth evaluation (RODRIGUES, 2008), being a work of a qualitative nature, with bibliographic, documentary and field research for theoretical and legal apprehension of the Social Assistance Policy, family and woman categories, also passing through by gender, intersectionality, poverty and social vulnerability. To account for the entanglement of the objectives, this evaluation followed the analytical dimensions proposed by the author Rodrigues (2008; 2011a; 2016): content analysis, institutional trajectories and temporal and territorial spectrum, in order to interpret the categories and regulatory frameworks present in the Social Assistance Policy, institutional discourses arising from direct observation and interviews with PAIF workers and tensions with the reality experienced by the subjects. From this perspective, it was reflected on the access and autonomy of the subjects and/or the renewal of conservatism and clientelism in social policies. Finally, we understand that there is no linear process in the construction of public policies in Brazil, even with all the legal and institutional apparatus that regulates them. We have observed, throughout history, that there are political and economic corporate projects that directly interfere in the implementation and implementation of public policies at the national and municipal levels. The dismantling of social policies is underway, and with the pandemic, this scenario is wide open, in view of: the precariousness of the work of SUAS professionals, the financial budget cut, the overvaluation of programs and benefits and, the centrality of individualized care in detriment of collective actions. In view of this, we conclude that the PAIF is a service that can offer possibilities of collective constructions for Social Assistance, however, like all services, programs and benefits, it faces difficulties in its execution and carries archaic remnants of assistentialism.